Description of Social Adjustment of Online Game Players in District: Gambaran Penyesuaian Sosial Pemain Game Online di Kecamatan - Firly Naffa Abas; Dwi Nastiti (Universitas Muhammadiyah Sidoarjo, 2022)
This research is motivated by the observations of researchers in a gaming environment where some online game players interact less with each other. This study aims to determine the description of the social adjustment of online game players in the Sananwetan sub-district, Blitar city. This research is a quantitative research problem with a descriptive approach with a single variable, namely the social adjustment variable. This research was conducted on gamers of the internet cafe manscave net and micophile net with a sample size of 150 players as permanent players in the cafe, which was taken using a simple random sampling technique which means that it provides equal opportunities for all elements (members) of the population to be selected as members of the population. sample members. Data analysis was carried out using descriptive statistical techniques using the SPSS 20 for windows program. The results of this research show that out of 150 online game players, 20.7% of online game players have good adjustment, 57.3% are sufficient, and 22% are less. Highlights: The study focuses on the social adjustment of online game players in the Sananwetan sub-district of Blitar city, motivated by observations of decreased interaction among players in a gaming environment. A quantitative research approach with a descriptive design was used, focusing on the single variable of social adjustment. The research involved a sample of 150 permanent players from internet cafes, selected through simple random sampling. The results revealed that 20.7% of players had good adjustment, 57.3% had sufficient adjustment, and 22% had lower levels of social adjustment. Keywords: online game players, social adjustment, quantitative research, descriptive approach, internet cafes